2015
DOI: 10.1165/rcmb.2014-0226tr
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin in Critical Illness

Abstract: Ghrelin, a recently described peptide, has attracted significant attention in recent years, primarily in the context of its endocrine- and appetite-regulating effects. The versatility of this peptide is manifested in a rapidly expanding body of literature highlighting its nonendocrine functions. This review summarizes the available data on the immunomodulatory as well as the non-immune-mediated effects of ghrelin that form the scientific basis of its role in critical illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 92 publications
0
18
0
Order By: Relevance
“…Here, we demonstrate that combined Ghr and GH treatment can modulate immune function in septic aged rats, which provides promising evidence of its therapeutic potential. Human Ghr has been administered to human subjects in more than 100 clinical studies covering various disease conditions and has demonstrated a very good safety profile [60]. Human GH has been approved by the Food and Drug Administration for the treatment of short stature due to GH deficiency in the pediatric population, chronic renal insufficiency, short bowel syndrome in adults, and AIDS-associated cachexia.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we demonstrate that combined Ghr and GH treatment can modulate immune function in septic aged rats, which provides promising evidence of its therapeutic potential. Human Ghr has been administered to human subjects in more than 100 clinical studies covering various disease conditions and has demonstrated a very good safety profile [60]. Human GH has been approved by the Food and Drug Administration for the treatment of short stature due to GH deficiency in the pediatric population, chronic renal insufficiency, short bowel syndrome in adults, and AIDS-associated cachexia.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we demonstrated that ghrelin reduced TGF-β levels in the serum in septic aged animals and ameliorated sepsis-induced immune suppression. Human ghrelin has been administered into human subjects in clinical studies, showing excellent e cacy and safety pro le (52). Ghrelin has 93% homology in its amino acid sequence between human and rat or human and mouse (53).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we demonstrated that ghrelin reduced TGF-β levels in the serum in septic aged animals and ameliorated sepsis-induced immune suppression. Human ghrelin has been administered into human subjects in clinical studies, showing excellent efficacy and safety profile (45). Ghrelin has 93% homology in its amino acid sequence between human and rat or human and mouse (46).…”
Section: Discussionmentioning
confidence: 99%